Immunogenomic characteristics and prognostic implications of terminally exhausted CD8+ T cells in colorectal cancers - Lee, Ji-Ae; Park, Hye Eun; Lee, Dae-Won; Han, Sae-Won; Kim, Tae-You; Jeong, Seung-Yong; Park, Kyu Joo; Bae, Jeong Mo; Kang, Gyeong Hoon (Frontiers in Immunology, 2025)
IntroductionT-cell exhaustion is a major mechanism of immune evasion. Recently, the therapeutic and prognostic implications of progenitor exhausted T cells (Tpex) and terminally exhausted T cells (Ttex) have been explored in various cancer types. This study explored the immunogenomic characteristics and prognostic implications of Tpex and Ttex in colorectal cancers (CRCs).MethodsWe performed multiplex immunofluorescence (mIF) using antibodies against CK, CD3, CD8, TCF1, and FOXP3 to assess diverse subsets of tumor-infiltrating lymphocytes (TILs) in 517 patients with stage III or high-risk stage II CRCs. We compared the infiltration level of these TIL subsets with the genetic profiles of CRCs, including microsatellite instability (MSI), tumor mutational burden (TMB), and mutations in 40 tumor-associated genes across five biological pathways.ResultsCD8+ T cell density, the CD8/CD3 ratio, and the Ttex/CD8+ T cell ratio were elevated in microsatellite instability-high and tumor mutational burden-high tumors. Survival analysis showed that, higher CD8+ T cell density, higher regulatory T cell/CD3+ T cell ratio, and higher Ttex/CD8+ T cell ratio exhibited better 5-year relapse-free survival (RFS) rates. When tumors were categorized into CD8-high, CD8-low/Ttex-low, and CD8-low/Ttex-high groups, the CD8-high and CD8-low/Ttex-high groups showed better 5-year RFS than the CD8-low/Ttex-low group.DiscussionTtex infiltration is associated with MSI and TMB status and may serve as a prognostic marker of CRCs.